The social and life skills menu : a skill building workbook for adolescents with autism spectrum disorders - Barber-Wada, Karra (Jessica Kingsley Publishers, 2011)
During adolescence social development and social status among peers is of crucial importance. For teenagers with Autism Spectrum Disorders (ASD) social interaction does not come naturally and often needs to be carefully learned. This workbook provides guided strategies to help those with ASD engage and connect with other people at home, school, work, social gatherings and in the community. Using a restaurant menu as a template, "The Social and Life Skills MeNu" guides readers through each step of a conversation with starter statements to initiate conversation, main course topics to c.